Effect of Sofosbuvir on Length of Hospital Stay in Moderate COVID-19 Cases; a Randomized Controlled Trial - Rama Bozorgmehr; Farbod Amiri; Mohammad Hosein Zade; Fariba Ghorbani; Arash Khameneh Bagheri; Esmat Yazdi; Sayyed Mojtaba Nekooghadam; Guitti Pourdowlat; Alireza Fatemi (Archives of Academic Emergency Medicine, 2022)
Introduction: Efforts to control the COVID-19 pandemic are still on. This study aimed to evaluate the effect of sofosbuvir on length of hospital stay and complications in COVID-19 cases with moderate severity.